The Parenting Patterns of Working Mother’s in Educating Children in Manarang District, Mattiro Bulu Sub-District, Pinrang District - Mutmainnah Arham; Muhammad Syukur; Idham Irwansyah Idrus; Najamuddin Najamuddin (International Journal of Science and Environment (IJSE), 2025)
This study aims to; 1) Analyze the parenting patterns of working mothers in educating their children in Manarang Subdistrict, Mattiro Bulu District, Pinrang Regency. 2) Analyze the factors influencing working mothers in choosing parenting patterns in educating their children in Manarang Subdistrict, Mattiro Bulu District, Pinrang Regency. 3) Analyze the impact of the parenting patterns of working mothers in educating their children in Manarang Subdistrict, Mattiro Bulu District, Pinrang Regency. The approach used is descriptive with a qualitative research type. Data collection was carried out through observation, interviews, and documentation. The informants consisted of working mothers and children whose mothers work, totaling 19 individuals selected using purposive sampling. The criteria for informants included mothers who perform dual roles as both caregivers and workers, and children whose mothers are employed. The data analysis technique consisted of three stages: data condensation, data display, and conclusion drawing. The research findings show that: 1) The parenting patterns of working mothers in Manarang Subdistrict vary, with mothers applying democratic parenting and mixed parenting styles. 2) Factors influencing the choice of parenting patterns among working mothers in Manarang include: a) Personality factors, b) Age factors, c) Educational background, and d) The parenting style received by the parents themselves. The impacts of working mothers’ parenting on child education in Manarang include: a) The child’s character is influenced both positively and negatively, b) Children’s learning motivation ranges from moderate to high.